Agronomic characteristics of white lupine and phosphorus contents after application of basalt rock dust associated with cover crops and microorganisms (Research, Society and Development, 2022)
Rock dust can be an alternative for improving soil chemical properties. Thus, the objective of the present study was to evaluate the yield components, phosphorus (P) contents in the white lupine plant and in the soil after application of basalt rock dust associated with cover crops and microorganisms. The experiment was conducted at the Experimental Station of the Universidade Estadual do Oeste do Paraná – UNIOESTE. The experimental design used was completely randomized blocks with 7 treatments and 4 replications. The treatments were: T1-Powder rock+green manure with Brachiaria; T2 - Rockdust + green manure with pigeon pea; T3 - Rock dust + Brachiaria + Azospirillum + Trichoderma + Pycnoporus; T4-Rock dust + Azospirillum; T5-Rock dust + Trichoderma; T6- Rock dust + Pycnoporus fungus; T7- Rock dust. The agronomic characteristics of white lupine cultivated in succession to the treatments and the phosphorus contents in the plant and in the soil were evaluated. The application of basalt rock powder together with brachiaria and pigeon pea it was beneficial the development of white lupine cultivated in succession and increased the availability of phosphorus in the soil. Among the microorganisms studied, the fungus of the genus Trichoderma applied together with the basalt rock powder was beneficial the production of dry mass of the aerial part of white lupine and was able to increase the availability of available phosphorus in the soil. Rock dust applied with Azospirillum also increased P availability in the soil. Meanwhile, the rock powder applied with Pycnoporus did not promote statistical difference for any of the evaluated characteristics.